2023
DOI: 10.3389/fendo.2023.1077846
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination trend and related factors among patients with diabetes in Korea: Analysis using a nationwide database

Abstract: BackgroundSubjects with diabetes are at higher risk of serious influenza-related complications. We aimed to investigate the yearly trend of influenza vaccination and factors associated with being unvaccinated for influenza in subjects with diabetes using a nationwide observational study performed within the recent decade.MethodsAmong 105,732 subjects from the Korea National Health and Nutrition Examination Survey between 2007 and 2019, 8,632 with diabetes were included. We investigated the yearly trend of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Regarding education level, findings from previous studies have been conflicting, particularly in relation to the association between education level and vaccination status. A study conducted in South Korea reported that individuals with higher education levels had lower vaccination rates[ 23 ]. In our study, we observed a non-statistically significant difference in vaccination status among individuals with varying educational levels, ranging from those below primary school to postgraduates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding education level, findings from previous studies have been conflicting, particularly in relation to the association between education level and vaccination status. A study conducted in South Korea reported that individuals with higher education levels had lower vaccination rates[ 23 ]. In our study, we observed a non-statistically significant difference in vaccination status among individuals with varying educational levels, ranging from those below primary school to postgraduates.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another study conducted in South Korea revealed that better glycemic control, evidenced by lower HbA1c levels, was associated with higher vaccine coverage. This was rationalized as poor glycemic control correlating with less adherence to medical advice and, therefore, lower vaccine coverage[ 23 ].…”
Section: Discussionmentioning
confidence: 99%